Positive electrode material, preparation method thereof and battery

By adopting a core-shell structure in the high-nickel single-crystal positive electrode material and combining elements of nickel, cobalt, manganese and aluminum, the problem of uneven Li ion concentration caused by the mixed Li/Ni is solved, and the electrochemical performance of the positive electrode material is significantly improved.

CN119852383AInactive Publication Date: 2025-04-18SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510327026.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The Li/Ni mixed discharge in high-nickel single-crystal cathode materials is severe, resulting in uneven Li ion concentration, resulting in intra-crystal cracks and deterioration of electrochemical properties.

Method used

The core-shell structure positive electrode material is adopted for matrix material and shell material. The matrix material includes nickel, cobalt and manganese elements, and the shell material includes aluminum and cobalt elements. By controlling the surface roughness and Li content, a structure with local high roughness and high lithium ion embedding points is formed.

Benefits of technology

It effectively improves the processing performance of the positive electrode material and the lithium ion migration performance, and improves the first-time efficiency, capacity and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852383A_ABST
    Figure CN119852383A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a preparation method thereof and a battery. The chemical general formula of the positive electrode material is aLigNixCoyMnzM1O2 * (1-a) LiaAlbCocO2, a is greater than 0.96 and less than 0.98, 0.9 lt, and a is greater than 0.96 and less than 0.98. A < lt >; 1, 1.2, 0.1 lt; blt; 0.2, 0.7 lt; clt; ct; 0.9, 0.98 < = g < = 1.01, 0.8 lt; xlt; 1, 0lt; yt; Yt; 0, 0, 0, 0; zlt, zlt; 0.2, x + y + z = 1, and M1 is a doping element; wherein NLi / Nm is larger than 0.98 and smaller than 1.00, NLi represents the molar weight of Li, and Nm represents the total molar weight of the nickel element, the cobalt element and the manganese element. According to the positive electrode material provided by the invention, the processing performance of the positive electrode material can be effectively improved, and a conductive agent and a binder can be attached to the surface of the material, so that the dispersity and uniformity of the positive electrode material in slurry are improved, and the charge transfer impedance of the lithium ion battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cathode materials, and in particular, to a cathode material, a preparation method thereof, and a battery. Background Art

[0002] Although high-nickel layered cathode materials have high specific capacity and working potential, the interfacial side reactions caused by high nickel content and residual lithium compounds lead to the loss of cathode active materials and the reduction of battery capacity. Due to the sensitivity of cathode materials to moisture and oxygen, the presence of LiOH, Li2CO3 and some adsorbed impurities on the cathode material makes the diffusion of Li + more difficult. The further reaction of Li2CO3 and LiOH with chain carbonate solvents will generate a large amount of gas, increase the resistance, cause rapid capacity degradation, and endanger the battery safety. With the increase of Ni content in nickel-rich materials, problems such as phase change, moisture sensitivity, side reaction, oxygen loss and mechanical instability appear. After cycling in harsh environments such as high voltage, oxygen release will be more obvious, and it will also have a significant impact on the battery in terms of thermal stability. There are a large number of structural defects and dislocations in the grain boundaries of the cathode material, resulting in an increase in the resistance of the grain boundary region and limiting the ionic conductivity. The surface coating layer of the cathode material is uneven, which is easy to form interface resistance and active sites for electrochemical reactions, and will also reduce the chemical stability of the battery. It can be seen that the surface chemical stability of the cathode material has an important impact on the performance of the battery.

[0003] In view of this, the present invention is specifically proposed. Summary of the Invention

[0004] The main object of the present invention is to provide a cathode material, a preparation method thereof, and a battery to solve the problem that the Li / Ni mixing of high-nickel single crystal materials in the prior art is serious, resulting in serious unevenness of Li ion concentration in space, thereby causing the generation of intracrystalline cracks and the deterioration of electrochemical performance.

[0005] To achieve the above object, according to one aspect of the present invention, a cathode material is provided. The cathode material includes a matrix material and a shell layer material at least partially coated on the surface of the matrix material. The matrix material includes nickel element, cobalt element and manganese element, and the shell layer material includes Al element and Co element. The cathode material satisfies: 6 < Rs / Ra ≤ 17.5, 300nm < Rs < 500nm, Ra is the surface average roughness of the cathode material, Rs is the surface maximum roughness of the cathode material, 0.98 < N Li / N m <1.00, N Li represents the molar amount of lattice Li in the cathode material per unit mass, N mRepresents the total molar amount of nickel, cobalt, and manganese elements in the positive electrode material per unit mass.

[0006] Furthermore, 28nm ≤ Ra < 50nm.

[0007] Furthermore, Q = 0.5 * Rs / Ra + 2.0 * N Li / N m , 5.5 ≤ Q ≤ 10.5.

[0008] Furthermore, 30nm ≤ Ra ≤ 40nm, 300nm < Rs < 400nm, and 8 < Rs / Ra < 13.5.

[0009] Furthermore, the surface residual lithium content of the positive electrode material < 1500ppm, preferably < 1200ppm.

[0010] Furthermore, the D50 of the positive electrode material is 2 - 8μm, preferably 3 - 5μm.

[0011] Furthermore, 0.4 ≤ S ≤ 0.8m 2 / g, where S is the specific surface area of the positive electrode material.

[0012] Furthermore, the positive electrode material is a single crystal material and includes grains with the same orientation, and the grain size is 0.5 - 3μm.

[0013] Furthermore, the tap density of the positive electrode material is: 1.2 ~ 1.9g / cm 3 .

[0014] Furthermore, the compaction density of the positive electrode material is: 2.8 ~ 3.3g / cm 3 .

[0015] Furthermore, N Li is 0.96 ~ 1.01mol.

[0016] Furthermore, the content of Al element in the positive electrode material is 1000 ~ 3000ppm.

[0017] Furthermore, the content of Co element in the positive electrode material is 30000 ~ 85000ppm.

[0018] Furthermore, the positive electrode material includes a matrix material of the core and a shell material at least partially coated on the surface of the core, and the chemical general formula of the matrix material is , and the chemical general formula of the shell material is Li a Al b Co c O2, and the chemical general formula of the positive electrode material is , where 0.96 < α < 0.98, 0.9 < a < 1.2, 0.1 < b < 0.2, 0.7 < c < 0.9, 0.98 ≤ ≤ 1.01, 0.8 < x < 1, 0 < y < 0.2, 0 < z < 0.2, x + y + z = 1, M1 is a doping element, and M1 is selected from at least one of A1, Co, Zr, B, Ti, Ca, Ce, Zn, Cr, Mg, Y, La, Sr, Ba, W, Mo, Nb, Si, and Sb.

[0019] According to another aspect of the present invention, a method for preparing a cathode material is further provided. The preparation method includes: Step S1, mixing a matrix material precursor, a lithium source, and an optional dopant, and performing a first calcination to obtain a first cathode material intermediate; Step S2, mixing the first cathode material intermediate with a cobalt source and an aluminum source, and performing a second calcination to obtain the cathode material; where the matrix material precursor is a nickel-cobalt-manganese ternary cathode material precursor; the dopant is selected from at least one of carbonates, hydroxides, hydroxyoxides, oxides, or acetates of M1.

[0020] Furthermore, the addition amount of the aluminum source satisfies: 0 < [n(Al)] / [n(Ni) + n(Co) + n(Mn)] ≤ 0.03, preferably 0.004 < [n(Al)] / [n(Ni) + n(Co) + n(Mn)] ≤ 0.01.

[0021] Furthermore, the addition amount of the cobalt source satisfies: 0 < [n(Co)] / [n(Ni) + n(Co) + n(Mn)] ≤ 0.04, preferably 0.01 < [n(Co)] / [n(Ni) + n(Co) + n(Mn)] ≤ 0.03.

[0022] Furthermore, the addition amount of the lithium source satisfies: 1.04 ≤ [n(Li)] / [n(Ni) + n(Co) + n(Mn)] ≤ 1.08, preferably 1.05 ≤ [n(Li)] / [n(Ni) + n(Co) + n(Mn)] ≤ 1.06.

[0023] Furthermore, the first cathode material intermediate satisfies: 1.02 ≤ [n(Li)] / [n(Ni) + n(Co) + n(Mn)] ≤ 1.06.

[0024] Further, step S2 includes: step S21, roughly crushing the first cathode material intermediate to obtain a roughly crushed material; step S22, finely pulverizing the roughly crushed material to obtain a second cathode material intermediate; step S23, mixing the second cathode material with a cobalt source and an aluminum source, and subjecting the mixture to a second roasting to obtain a cathode material; wherein, the roughly crushed material satisfies: 1.03 ≤ [n(Li)] / [n(Ni)+n(Co)+n(Mn)] ≤ 1.06, preferably 1.04 ≤ [n(Li)] / [n(Ni)+n(Co)+n(Mn)] ≤ 1.05; the second cathode material intermediate satisfies: 1.02 ≤ [n(Li)] / [n(Ni)+n(Co)+n(Mn)] ≤ 1.04, preferably 1.025 ≤ [n(Li)] / [n(Ni)+n(Co)+n(Mn)] ≤ 1.035.

[0025] According to the third aspect of the present invention, a battery is provided, which includes the cathode material provided in the first aspect or the cathode material obtained by the preparation method provided by the core-shell cathode material provided in the second aspect.

[0026] Applying the technical solution of the present application, for the cathode material provided by the present application, its maximum surface roughness Rs and surface average roughness Ra satisfy 6 < Rs / Ra ≤ 17.5, indicating that there are local areas on the surface of the cathode material with roughness much greater than other areas. Thus, the relatively high-roughness areas can effectively improve the processing performance of the cathode material, facilitate the attachment of conductive agents and binders to the material surface, and further improve the dispersibility and uniformity of the cathode material in the slurry, reducing the charge transfer impedance of the lithium-ion battery. At the same time, the relatively low roughness formed in other areas of the cathode material indicates that this area has a larger specific surface area and can generate more lithium-ion insertion points. The two work together to optimize the lithium-ion migration performance of the cathode material while ensuring the processing performance of the cathode material. And the cathode material in the present application includes a matrix material and at least part of a shell material coated on the surface of the matrix material. At the same time, further control 0.98 < N Li / N m <1.00, so that the residual Li on the surface of the shell material reacts with the Co compound, and the lattice Li in the matrix material is not consumed by Co, so that the cathode material provided by the present application has both partial areas with high roughness and a certain lattice Li content, synergistically promoting the migration of lithium ions within the cathode particles, and thus having high initial efficiency, capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The specification drawings constituting a part of the present application are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0028] Figure 1 A schematic diagram of the structure of a battery during charging provided in some embodiments of the present application;

[0029] Figure 2 A schematic diagram of the structure of a battery during discharge provided in some embodiments of the present application;

[0030] Figure 3 shows a SEM image of the positive electrode material provided in Example 1;

[0031] Figure 4 The SEM image of the positive electrode material provided in Comparative Example 1 is shown;

[0032] Figure 5 The SEM image of the positive electrode material provided in Comparative Example 2 is shown;

[0033] Figure 6 The SEM image of the positive electrode material provided in Comparative Example 6 is shown;

[0034] Figure 7 The SEM image of the positive electrode material provided in Comparative Example 7 is shown. DETAILED DESCRIPTION

[0035] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0036] As analyzed in the background technology of this application, the cycle performance of single crystal positive electrode materials is excellent, but the coulombic efficiency of the first cycle is low, which is mainly due to Li / Ni mixing, especially the Li / Ni mixing of high nickel single crystal materials is more serious, mainly because the excessively high sintering temperature easily leads to serious Li / Ni mixing and irreversible oxygen loss, which causes serious Li ion concentration inhomogeneity in space, and then leads to the generation of intracrystalline cracks and the deterioration of electrochemical performance. In order to solve these problems, the present application provides a positive electrode material, a preparation method thereof and a secondary battery.

[0037] In a first typical embodiment of the present application, a positive electrode material is provided, the positive electrode material comprising a base material and a shell material at least partially coated on the surface of the base material, the base material comprising nickel, cobalt and manganese, the shell material comprising Al and Co, the surface average roughness of the positive electrode material is represented by Ra, the surface maximum roughness is represented by Rs, 6 <Rs / Ra≤17.5;0.98<N Li / N m <1.00, N Li Indicates the molar amount of lattice Li in unit mass of positive electrode material, N mIt represents the total molar amount of nickel element, cobalt element and manganese element in the cathode material per unit mass.

[0038] It should be noted that in this application, the molar amount of lattice Li refers to the total molar amount of lithium in the cathode material minus the molar amount of residual lithium on the surface; both the surface average roughness and the surface maximum roughness are measured by an atomic force microscope.

[0039] In this application, the method for measuring the surface average roughness of the cathode material is as follows: the surface of the cathode material is divided into 10 regions with equal areas, 6μm×6μm test regions are taken from each of the 10 regions, and the average value of the surface roughness of the 10 test regions is measured respectively by the probe of the atomic force microscope; the average values of the surface roughness of the 10 test regions are added and then averaged to obtain the surface average roughness of the cathode material.

[0040] The method for measuring the surface maximum roughness of the cathode material is as follows: the maximum value of the surface roughness of the above 10 test regions is measured respectively by the probe of the atomic force microscope, and the surface roughness of the 10 test regions is added and then averaged to obtain the surface maximum roughness of the cathode material.

[0041] For the cathode material provided in this application, when its surface maximum roughness Rs and surface average roughness Ra satisfy 6 < Rs / Ra ≤ 17.5, it indicates that there are local regions on the surface of the cathode material with roughness much greater than other regions. Therefore, the higher roughness regions can effectively improve the processing performance of the cathode material, facilitate the attachment of conductive agents and binders to the material surface, and further improve the dispersibility and uniformity of the cathode material in the slurry, reducing the charge transfer impedance of the lithium-ion battery. At the same time, the lower roughness formed in other regions of the cathode material indicates that this region has a larger specific surface area and can generate more lithium-ion insertion points. The two work together to optimize the lithium-ion migration performance of the cathode material on the basis of ensuring the processing performance of the cathode material. And the cathode material in this application includes a matrix material and at least part of a shell material coated on the surface of the matrix material. At the same time, further control 0.98 < N Li / N m <1.00, so that the residual Li on the surface of the shell material reacts with the Co compound, and the lattice Li in the matrix material is not consumed by Co, so that the cathode material provided in this application has both high roughness in some regions and a certain lattice Li content, synergistically promoting the migration of lithium ions within the cathode particles, and thus having high initial efficiency, capacity and cycle stability.

[0042] Specifically, in the positive electrode material provided by the present application, 300 nm < Rs < 500 nm. Rs can be 301 nm, 302 nm, 305 nm, 310 nm, 312 nm, 320 nm, 350 nm, 368 nm, 378 nm, 380 nm, 385 nm, 390 nm, 400 nm, 410 nm, 415 nm, 420 nm, 450 nm, 480 nm, 489 nm, 490 nm, 495 nm, 498 nm, 499 nm or a range value composed of any two numerical values. The higher roughness region can effectively improve the processing performance of the positive electrode material, facilitate the attachment of the conductive agent and the binder to the material surface, and thus improve the dispersibility and uniformity of the positive electrode material in the slurry.

[0043] Rs / Ra can be 6.01, 6.10, 6.15, 6.55, 6.6, 6.85, 7.00, 8.00, 9.00, 9.55, 10.00, 10.22, 10.26, 10.64, 10.81, 11.0, 11.1, 11.14, 11.39, 11.7, 12.00, 13.5, 15.00, 16.00, 16.6, 17.0, 17.2, 17.4, 17.5 or a range value composed of any two numerical values.

[0044] In some embodiments, in the positive electrode material provided by the present application, 28 nm ≤ Ra < 50 nm, so as to facilitate the surface roughness of the positive electrode material to be in a suitable range, further promote the generation of more lithium ion insertion points in the positive electrode material, and improve the rate performance of the battery. Specifically, Ra can be 28 nm, 29 nm, 29.5 nm, 30 nm, 30.0 nm, 30.5 nm, 31 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, 40 nm, 42 nm, 45 nm, 47 nm, 48 nm, 49.5 nm or a range value composed of any two numerical values.

[0045] In some embodiments, Q = 0.5 * Rs / Ra + 2.0 * N Li / N m , 5.5 ≤ Q ≤ 10.5. Controlling the positive electrode material to satisfy the above relationship is beneficial to ensuring the dispersibility and uniformity of the positive electrode material in the slurry brought by the high roughness, while also synergistically exerting the high active sites and lattice lithium content brought by the low roughness to further promote the lithium ion migration rate, so that the positive electrode material has both capacity, initial efficiency and cycle stability. Specifically, Q can be 5.5, 5.8, 6.0, 6.2, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5 or a range value composed of any two numerical values.

[0046] In some embodiments, 30nm ≤ Ra ≤ 40nm, 300nm < Rs < 400nm, and 8 < Rs / Ra < 13.5, which is more conducive to improving the processing performance of the cathode material due to the relatively high roughness of the shell part, and more conducive to the attachment of conductive agents and binders to the surface of the material, improving the dispersibility and uniformity of the cathode material in the slurry. At the same time, other regions have relatively low roughness, which is more conducive to generating more lithium ion insertion points, thereby more conducive to reducing the charge transfer impedance of the lithium ion battery and improving the rate performance.

[0047] In some embodiments, the residual lithium on the surface of the cathode material is < 1500ppm, which is conducive to reducing the occurrence of side reactions on the surface of the cathode material, further reducing the loss of the cathode active material, and thus improving the capacity of the cathode material. Especially when the residual lithium on the surface of the cathode material is < 1200ppm, it is more conducive to improving the capacity of the cathode material.

[0048] In some embodiments, the volume median diameter D50 of the cathode material is 2 - 8μm, with a more uniform particle size, which is more conducive to its dispersion in the slurry and also more conducive to improving the compaction density of the cathode sheet, and thus more conducive to improving the capacity of the battery. Specifically, the D50 of the cathode material can be 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 7μm, 8μm or a range value composed of any two numerical values.

[0049] In some embodiments, the cathode material satisfies: 0.4 ≤ S ≤ 0.8m 2 / g, where S is the specific surface area of the cathode material, and its particle size is more moderate, which is more conducive to the dispersion of the cathode material in the slurry, and thus more conducive to improving the dispersion uniformity of the cathode material in the cathode sheet. Specifically, S can be 0.4m 2 / g, 0.45m 2 / g, 0.5m 2 / g, 0.55m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 / g, 0.75m 2 / g, 0.8m 2 / g or a range value composed of any two numerical values.

[0050] In some embodiments, the cathode material is a single crystal material and includes grains with the same orientation, and the grain size is 0.5 - 3μm, which is conducive to making its structure more regular and improving the chemical stability of the battery. Specifically, the grain size can be 0.5μm, 0.8μm, 1.0μm, 1.2μm, 1.5μm, 2.0μm, 2.2μm, 2.5μm, 2.8μm, 3.0μm or a range value composed of any two numerical values.

[0051] In the present application, the particle size of the crystal grains is measured by observing the cross section of the positive electrode material using a scanning electron microscope; the particle size of the positive electrode material is measured by a particle size analyzer.

[0052] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nano-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD (backscattered electron diffraction technology) testing method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict sense of crystallography. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and orientation. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.

[0053] The cycle performance of single crystal cathode materials is excellent, but the Coulomb efficiency of the first cycle is low. The main reason is Li / Ni mixing, especially the Li / Ni mixing of high nickel single crystal materials is more serious. This is mainly because the excessively high sintering temperature can easily lead to serious Li / Ni mixing and irreversible oxygen loss, which causes serious Li ion concentration inhomogeneity in space, leading to the generation of intracrystalline cracks and deterioration of electrochemical performance. The Co element can promote the growth of single crystals and inhibit the occurrence of Li / Ni mixing in high nickel single crystal materials. Composite Co coating of high nickel single crystal materials is an important way to improve high nickel single crystal cathode materials, but the amount of Co coating has an important influence on the capacity of the material; in addition, single coating of Co cannot improve the single crystal cycle because Co is dissolved. Composite coating of Co with other elements is an important aspect of improving high nickel single crystal materials.

[0054] In some embodiments, the positive electrode material includes a base material and a shell material at least partially coated on the surface of the base material. The general chemical formula of the base material is The chemical formula of the shell material is Li a Alb Co c O2, and the chemical general formula of the positive electrode material is , where 0.96 < α < 0.98, 0.9 < a < 1.2, 0.1 < b < 0.2, 0.7 < c < 0.9, 0.98 ≤ ≤ 1.01, 0.8 < x < 1, 0 < y < 0.2, 0 < z < 0.2, x + y + z = 1, M1 is a doping element, and M1 is selected from at least one of A1, Co, Zr, B, Ti, Ca, Ce, Zn, Cr, Mg, Y, La, Sr, Ba, W, Mo, Nb, Si, and Sb. By setting the positive electrode material as a core - shell structure, the shell material is more stable than the matrix material, so that the residual Li on the surface of the shell material reacts with the Co compound, and the lattice Li is not consumed by Co, thus enabling the positive electrode material provided in this application to have both a high roughness in some regions and a certain lattice Li content, and therefore having a high initial efficiency, capacity, and cycle stability.

[0055] In this application, it can be shown that the positive electrode material has an obvious core - shell structure by characterizing the particle cross - section of the positive electrode material through EDS. Specifically, by means of EDS line scanning to test the contents of Al element and Co element in the positive electrode material particles, from the edge of the positive electrode material particles to the center of the positive electrode material particles, in the region where the shell transitions to the matrix material, the content of Al element or Co element rapidly decreases and then tends to be stable. The region where the content of Al element and Co element tends to be stable after decreasing is the matrix material, and the region where Al and Co elements rapidly decrease and are close to the surface is the shell structure.

[0056] In some embodiments, the tap density of the positive electrode material is: 1.2~1.9 g / cm 3 . Specifically, the tap density of the positive electrode material can be 1.2 g / cm 3 , 1.3 g / cm 3 , 1.4 g / cm 3 , 1.5 g / cm 3 , 1.6 g / cm 3 , 1.7 g / cm 3 , 1.8 g / cm 3 , 1.9 g / cm 3 or any value within the above range.

[0057] In some embodiments, the compression density of the positive electrode material is: 2.8~3.3 g / cm 3 . Specifically, the compression density of the positive electrode material can be 2.8 g / cm 3 , 2.9 g / cm 3 , 3.0 g / cm 3 , 3.1 g / cm3 、3.2 g / cm 3 、3.3 g / cm 3 Or any value within the above range.

[0058] In some embodiments, N Li Specifically, the molar content of lattice lithium per unit mass of the positive electrode material may be 0.96, 0.97, 0.98, 0.99, 1, 1.01 mol or any value within the above range.

[0059] In some embodiments, based on the total mass of the positive electrode material, the content of Al in the positive electrode material is 1000-3000 ppm. Specifically, the content of Al in the positive electrode material is 1000 ppm, 1300 ppm, 1500 ppm, 1700 ppm, 1800 ppm, 2000 ppm, 2100 ppm, 2300 ppm, 2400 ppm, 2500 ppm, 2700 ppm, 2900 ppm, 3000 ppm or any value within the above range.

[0060] In some embodiments, based on the total mass of the positive electrode material, the content of Co in the positive electrode material is 30000 ppm to 85000 ppm. Specifically, the content of Co in the positive electrode material is 30000, 40000, 50000, 60000, 70000, 80000, 85000 or any value within the above range.

[0061] In a second typical embodiment of the present application, a method for preparing the positive electrode material provided in the above-mentioned first typical embodiment is also provided, and the preparation method includes: step S1, mixing a matrix material precursor, a lithium source and an optional dopant M1, and obtaining a first positive electrode material intermediate through a first calcination; step S2, mixing the first positive electrode material intermediate with a cobalt source and an aluminum source, and obtaining a positive electrode material through a second calcination; wherein the matrix material precursor is a nickel-cobalt-manganese ternary positive electrode material precursor; and the dopant is selected from at least one of M1 carbonate, hydroxide, oxyhydroxyl, oxide and acetate.

[0062] The positive electrode material provided in the present application is first mixed with a base material precursor, a lithium source and an optional dopant, subjected to a first calcination, and then mixed with a cobalt source and an aluminum source for a second calcination, thereby preparing a positive electrode material with a base material as a core and a shell material at least partially coated on the surface of the core. In the second calcination process, a cobalt source and an Al source are mixed with a second positive electrode material intermediate for sintering to partially enrich Al and Co on the surface of the base material, thereby forming a high roughness in some areas and reducing the consumption of lattice Li.

[0063] In some embodiments, the amount of aluminum source added satisfies: 0<[n(Al)] / [n(Ni)+n(Co)+n(Mn)]≤0.03, so as to facilitate the preparation of a composite lithium cobalt lithium oxide with higher roughness, thereby improving the processing performance of the positive electrode material.

[0064] In the present application, n(Al), n(Ni), n(Co), n(Mn), and n(Li) refer to the molar amounts of Al, Ni, Co, Mn, and Li, respectively.

[0065] In some embodiments, the amount of cobalt source added satisfies: 0<[n(Co)] / [n(Ni)+n(Co)+n(Mn)]≤0.04, preferably 0.01<[n(Co)] / [n(Ni)+n(Co)+n(Mn)]≤0.03, so as to suppress Li / Ni rearrangement while having excellent capacity performance.

[0066] In some embodiments, the amount of lithium source added satisfies: 1.04≤[n(Li)] / [n(Ni)+n(Co)+n(Mn)≤1.08, preferably 1.05≤[n(Li)] / [n(Ni)+n(Co)+n(Mn)]≤1.06, so as to further improve the capacity, cycle performance and first effect of the positive electrode material.

[0067] In some embodiments, the first positive electrode material intermediate satisfies 1.02≤[n(Li)] / [n(Ni)+n(Co)+n(Mn)]≤1.06 to further control the content of lattice Li in the core-shell positive electrode material and the residual Li content on the surface of the first positive electrode material intermediate to provide sufficient residual lithium for subsequent Al and Co to react, thereby ensuring the lattice lithium content in the positive electrode material, thereby further improving the capacity and cycle stability of the positive electrode material.

[0068] In order to further improve the uniformity of dispersion of various elements in the positive electrode material, in some embodiments, step S2 includes: step S21, coarsely crushing the first positive electrode material intermediate to obtain a coarsely crushed material; step S22, finely crushing the coarsely crushed material to obtain a second positive electrode material intermediate; step S23, mixing the second positive electrode material with an optional cobalt source and an optional aluminum source, and obtaining a positive electrode material through a second calcination.

[0069] In the above step S21, the method of rough crushing is not limited. From the perspective of improving the rough crushing efficiency, it is preferred to use a roller machine for rough crushing. In some specific embodiments, the conditions for rough crushing include: the roller gap of the roller machine is 2.0-5.0 mm, the particle size D50 of the rough crushed material is 2.0-5.0 mm; the cross section of the gas crushed material is observed by high-power SEM within the range of 20μm*20μm, and the number of particles with cracks inside the particles is less than 3. The above crushing conditions are conducive to reducing the loss of lattice lithium in the positive electrode material to ensure the lattice lithium content in the positive electrode material.

[0070] In the above step S22, there is no limitation on the method of fine grinding. From the perspective of improving the efficiency of fine grinding, it is preferred to use air flow grinding to perform fine grinding, reverse breaking and sieving to obtain a second positive electrode material intermediate with a particle size D50 of 3-5 μm.

[0071] In order to further improve the efficiency of the first roasting, in some embodiments, the temperature T1 of the first roasting is preferably 600-1200°C, and the time is 10-30h. Specifically, the temperature T1 of the first roasting can be 600°C, 650°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, or a range value consisting of any two values, and the time of the first roasting can be 10h, 12h, 15h, 18h, 20h, 22h, 25h, 28h, 30h, or a range value consisting of any two values.

[0072] In some embodiments, the first sintering atmosphere is oxygen, so as to facilitate the formation of a matrix material with better performance.

[0073] In order to further improve the uniform dispersion of the internal elements in the matrix material and reduce the loss of lattice lithium, the first calcination includes a first insulation section and a second insulation section, wherein the temperature T1-1 of the first insulation section satisfies 800<T1-1≤1200℃, the insulation time of the first insulation section is t1, the temperature T1-2 of the second insulation section satisfies 600≤T1-2≤800℃, the insulation time of the second insulation section is t2, 2<t1 / t2<9, preferably 3<t1 / t2<5. Specifically, t1 / t2 can be 2.1, 2.5, 3, 3.2, 3.5, 3.8, 4.0, 4.2, 4.5, 4.8, 5, 7, 9 or a range of any two values.

[0074] During the above-mentioned second roasting process, the upper shell material is coated on at least part of the surface of the base material. In order to further improve the efficiency of the second roasting, in some embodiments, the second roasting includes a third insulation section and a fourth insulation section, wherein the temperature T2-1 of the third insulation section satisfies 650<T2-1≤850℃, the insulation time of the third insulation section is t3, 5h<t3≤10h, the temperature T2-2 of the fourth insulation section satisfies 500≤T2-2≤650℃, the insulation time of the third insulation section is t4, 1h<t4≤5h, 1<t3 / t4<4, preferably 1.5<t3 / t4<3.5. Specifically, t3 / t4 can be 1.05, 1.2, 1.5, 1.8, 2.0, 2.2, 2.5, 2.8, 3.0, 3.2, 3.5, 3.8, 3.95 or a range value consisting of any two values.

[0075] In the above-mentioned second calcination process, a cobalt source and an Al source are mixed with the second positive electrode material intermediate for sintering, and the second calcination temperature is relatively low. At the same time, the Ni content in the matrix material is relatively high, and Al and Co are difficult to be doped into the material. At the same time, Al will also inhibit Co from entering the matrix material, thereby causing Al and Co to be partially enriched on the surface of the matrix material, forming high roughness in some areas.

[0076] In some embodiments, the atmosphere of the second calcination is an oxygen-containing atmosphere, and preferably the oxygen-containing atmosphere is air and / or oxygen.

[0077] In a third typical embodiment of the present application, a battery is provided, which includes a positive electrode material. The positive electrode material includes the positive electrode material provided in the first typical embodiment or the positive electrode material obtained according to the preparation method provided in the second typical embodiment.

[0078] The battery provided in the present application uses a positive electrode material having both high roughness in some areas and a certain lattice Li content as the positive electrode material, has high first efficiency, capacity and cycle stability, and has broad application prospects.

[0079] In some embodiments, Figure 1 and Figure 2 As shown, the battery includes a housing and an electrode assembly, the electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator, and the separator is arranged between the positive electrode sheet and the negative electrode sheet. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.

[0080] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector.

[0081] In some embodiments, the positive electrode current collector may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active layer includes the positive electrode active material as described above.

[0082] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector.

[0083] In some embodiments, the negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer includes a negative electrode material, and the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery may be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which are not limited here.

[0084] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0085] Example 1

[0086] This embodiment provides a positive electrode material, which is prepared according to the following steps:

[0087] (1) Ni-Co-Mn hydroxide precursor Ni 0.83 Co 0.12 Mn 0.5(OH)2, lithium hydroxide, and aluminum oxide are uniformly mixed in a molar ratio of n(Li):n(Al): [n(Ni)+n(Co)+n(Mn)]=1.05:0.001:1, and a first sintering is performed under an oxygen atmosphere, wherein the first sintering includes a first insulation section and a second insulation section, wherein the temperature T1-1 of the first insulation section is 875°C, the insulation time t1 is 9h, the temperature T1-2 of the second insulation section is 720°C, the insulation time t2 is 4h, and the mixture is naturally cooled to room temperature to obtain a first positive electrode material intermediate. After testing, the residual Li content on the surface of the first positive electrode material intermediate is 3000ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn) is 1.0 as determined by ICP (inductively coupled plasma emission spectrometer) potentiometric titration.

[0088] (2) The first cathode material intermediate is put into a roller mill with a roller gap of 3 mm to obtain a roller material with a particle size D50 of 3 mm. The roller material is put into an air flow mill with a volume ratio of 40-60% in the air flow mill chamber and an air pressure of 450 kPa < P < 550 kPa. The particle size D50 of the air flow mill material is 3.5 ± 0.5 μm. The second cathode material intermediate is obtained: Li 1.03 Ni 0.83 Co 0.12 Mn 0.05 Al 0.001 O2;

[0089] (3) The second positive electrode material intermediate, aluminum oxide, and cobalt oxide are uniformly mixed in a molar ratio of n(Al):n(Co):[n(Ni)+n(Co)+n(Mn)]=0.01:0.03:1, and a second calcination is performed under an oxygen atmosphere, wherein the second calcination includes a third insulation stage and a fourth insulation stage, the temperature T2-1 of the third insulation stage is 720°C, the insulation time t3 is 10h, the temperature T2-2 of the fourth insulation stage is 600°C, the insulation time t4 is 5h, and the mixture is naturally cooled to room temperature and sieved to obtain a positive electrode material.

[0090] Example 2

[0091] The difference between this embodiment and embodiment 1 is that in step (1), the insulation time t2 of the second insulation stage is 2 hours. The residual Li content on the surface of the first positive electrode material intermediate is 3900 ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn)=0.992.

[0092] Example 3

[0093] The difference between this embodiment and embodiment 1 is that in step (1), titanium dioxide (TiO2) is used instead of aluminum oxide as a dopant. The residual Li content on the surface of the first positive electrode material intermediate is 3200 ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn)=0.996.

[0094] Example 4

[0095] The difference between this embodiment and embodiment 1 is that in step (1), zirconium dioxide (ZrO2) is used to replace aluminum oxide as a dopant. The residual Li content on the surface of the first positive electrode material intermediate is 3300 ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn)=0.997.

[0096] Example 5

[0097] The difference between this embodiment and embodiment 1 is that in step (1), yttrium oxide (Y2O3) is used to replace aluminum oxide as a dopant. The residual Li content on the surface of the first positive electrode material intermediate is 3300 ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn)=0.998.

[0098] Example 6

[0099] The difference between this embodiment and embodiment 1 is that in step (1), the nickel-cobalt-manganese hydroxide precursor Ni 0.83 Co 0.12 Mn 0.5 (OH)2, lithium hydroxide, and aluminum oxide are uniformly mixed in a molar ratio of n(Li):n(Al): [n(Ni)+n(Co)+n(Mn)]=1.06:0.001:1, and the insulation time t2 of the second insulation stage is 2h. The residual Li content on the surface of the first positive electrode material intermediate is 3700ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn) is 0.998.

[0100] Example 7

[0101] The difference between this embodiment and embodiment 1 is that in step (1), the nickel-cobalt-manganese hydroxide precursor Ni 0.83 Co 0.12 Mn 0.5(OH)2, lithium hydroxide, and aluminum oxide are uniformly mixed in a molar ratio of n(Li):n(Al): [n(Ni)+n(Co)+n(Mn)]=1.04:0.001:1. The residual Li content on the surface of the first positive electrode material intermediate is 3100ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn) is 0.994.

[0102] Example 8

[0103] The difference between this embodiment and embodiment 1 is that in step (1), the nickel-cobalt-manganese hydroxide precursor Ni 0.83 Co 0.12 Mn 0.5 (OH)2, lithium hydroxide, and aluminum oxide are uniformly mixed in a molar ratio of n(Li):n(Al): [n(Ni)+n(Co)+n(Mn)]=1.04:0.0005:1. The residual Li content on the surface of the first positive electrode material intermediate is 3300ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn) is 0.995.

[0104] Example 9

[0105] The difference between this embodiment and embodiment 1 is that in step (1), the nickel-cobalt-manganese hydroxide precursor Ni 0.83 Co 0.12 Mn 0.5 (OH)2, lithium hydroxide, and aluminum oxide are uniformly mixed in a molar ratio of n(Li):n(Al): [n(Ni)+n(Co)+n(Mn)]=1.04:0.0015:1. The residual Li content on the surface of the first positive electrode material intermediate is 3150ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn) is 0.993.

[0106] Example 10

[0107] The difference between this embodiment and embodiment 1 is that in step (1), the nickel-cobalt-manganese hydroxide precursor Ni 0.83 Co 0.12 Mn 0.5 (OH)2, lithium hydroxide, and aluminum oxide are uniformly mixed in a molar ratio of n(Li):n(Al): [n(Ni)+n(Co)+n(Mn)]=1.04:0.002:1, and the insulation time t2 of the second insulation stage is 2h. The residual Li content on the surface of the first positive electrode material intermediate is 3400ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn) is 0.997.

[0108] Embodiment 11

[0109] The difference between this embodiment and embodiment 1 is that in step (1), the temperature T1-1 of the first insulation stage is 865° C. The residual Li content on the surface of the first positive electrode material intermediate is 3300 ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn)]=0.995.

[0110] Example 12

[0111] The difference between this embodiment and embodiment 1 is that in step (1), the temperature T1-1 of the first insulation stage is 885° C. The residual Li content on the surface of the first positive electrode material intermediate is 3250 ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn)=0.996.

[0112] Example 13

[0113] The difference between this embodiment and embodiment 1 is that in step (1), the insulation time t1 of the first insulation stage is 7 hours. The residual Li content on the surface of the first positive electrode material intermediate is 3100 ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn)=0.998.

[0114] Embodiment 14

[0115] The difference between this embodiment and embodiment 1 is that in step (1), the insulation time t1 of the first insulation stage is 11 hours. The residual Li content on the surface of the first positive electrode material intermediate is 3400 ppm, and the lattice Li satisfies n(Li)] / [n(Ni)+n(Co)+n(Mn)=0.993.

[0116] Comparative Example 1

[0117] This comparative example provides a positive electrode material, which is prepared according to the following steps:

[0118] (1) Ni-Co-Mn hydroxide precursor Ni 0.83 Co 0.12 Mn 0.5 (OH)2, lithium hydroxide, and aluminum oxide are uniformly mixed in a ratio of n(Li):n(Al): [n(Ni)+n(Co)+n(Mn)]=1.05:0.001:1, and the first calcination is carried out under an oxygen atmosphere. The first calcination includes a first insulation section and a second insulation section, wherein the temperature T1-1 of the first insulation section is 875°C, and the insulation time t1 is 9h, the temperature T1-2 of the second insulation section is 720°C, and the insulation time t2 is 4h, and the mixture is naturally cooled to room temperature to obtain a first positive electrode material intermediate.

[0119] (2) The first cathode material intermediate is put into a roller mill with a roller gap of 3 mm to obtain a roller material with a particle size D50 of 3 mm. The roller material is put into an air flow mill to control the volume of the material in the air crushing chamber to account for 40-60%, the air pressure of the air crusher is 450 kPa<P<550 kPa, and the particle size of the air crushing material is D50=3.5±0.5 um; the second cathode material intermediate is obtained: Li 1.03 Ni 0.83 Co 0.12 Mn 0.05 Al 0.001 O2.

[0120] (3) The second positive electrode material intermediate and alumina are uniformly mixed in a ratio of n(Al):[n(Ni)+n(Co)+n(Mn)]=0.01:1, and a second calcination is performed under an oxygen atmosphere. The second calcination includes a third insulation stage and a fourth insulation stage. The temperature T2-1 of the third insulation stage is 720°C, and the insulation time t3 is 10 h. The temperature T2-2 of the fourth insulation stage is 600°C, and the insulation time t4 is 5 h. The mixture is naturally cooled to room temperature and sieved to obtain the positive electrode material.

[0121] Comparative Example 2

[0122] The difference between this comparative example and Example 1 is that in step (3), the second positive electrode material intermediate and titanium dioxide are uniformly mixed in a molar ratio of n(Ti):[n(Ni)+n(Co)+n(Mn)]=0.01:1.

[0123] Comparative Example 3

[0124] The difference between this comparative example and Example 1 is that in step (3), the second positive electrode material intermediate, titanium dioxide, and zirconium dioxide are uniformly mixed in a molar ratio of n(Ti): n(Zr):[n(Ni)+n(Co)+n(Mn)]=0.01: 0.01: 1.

[0125] Comparative Example 4

[0126] The difference between this comparative example and Example 1 is that in step (1), the insulation time t2 of the second insulation section is set to 0 h.

[0127] Comparative Example 5

[0128] The difference between this comparative example and Example 1 is that in step (3), the insulation time t3 of the third insulation section is set to 5 h.

[0129] Comparative Example 6

[0130] The difference between this comparative example and Example 1 is that in step (3), the coating agents aluminum oxide and cobalt oxide are replaced by TiO2 and Co3O4, and n(Ti):n(Co):[n(Ni)+n(Co)+n(Mn)]=0.01: 0.03: 1.

[0131] Comparative Example 7

[0132] The difference between this comparative example and Example 1 is that in step (3), the coating agents aluminum oxide and cobalt oxide are replaced by ZrO2 and Co3O4, n(Zr):n(Co):[n(Ni)+n(Co)+n(Mn)]=0.01: 0.03: 1.

[0133] Comparative Example 8

[0134] The difference between this comparative example and Example 1 is that in step (3), the coating agents aluminum oxide and cobalt oxide are replaced by WO3 and Co3O4, n(W):n(Co):[n(Ni)+n(Co)+n(Mn)]=0.01: 0.03: 1.

[0135] Comparative Example 9

[0136] The difference between this comparative example and Example 1 is that in step (3), the coating agents aluminum oxide and cobalt oxide are replaced by Co3O4, and n(Co):[n(Ni)+n(Co)+n(Mn)]=0.03:1.

[0137] Comparative Example 10

[0138] The difference between this comparative example and Example 1 is that in step (3), n(Al):n(Co):[n(Ni)+n(Co)+n(Mn)]=0.005: 0.015: 1.

[0139] Comparative Example 11

[0140] The difference between this comparative example and Example 1 is that in step (3), n(Al):n(Co):[n(Ni)+n(Co)+n(Mn)]=0.02: 0.06: 1.

[0141] Test example

[0142] The positive electrode materials provided in the above embodiments and comparative examples were subjected to performance tests, and the results are shown in Tables 1 and 2 below.

[0143] (1) Morphology test

[0144] The surface morphology of the material was characterized by a Hitachi S4800 field emission scanning electron microscope with an accelerating voltage of 3 kV.

[0145] (2) Residual alkali (LiOH, Li2CO3) and surface residual lithium test

[0146] Take 5g of positive electrode material sample and disperse it in 100mL of deionized water, and dissolve the residual carbonate and hydroxide by magnetic stirring. After filtration, the filtrate is obtained, and hydrochloric acid solution is added to the automatic potentiometric titrator, and titrated in an equivalent dropwise manner. The mass content of lithium carbonate and lithium hydroxide of the positive electrode material is calculated by the situation of the breakthrough point and the degree of consumption of the hydrochloric acid solution. The residual lithium content on the surface is obtained by multiplying the mass content of lithium carbonate and lithium hydroxide by the mass ratio of lithium in lithium carbonate and lithium hydroxide.

[0147] (3) Element (Li, Co, Ni and Mn) content test

[0148] The content of various metal elements in the positive electrode material was tested by ICP. The Agilent 5800 ICP spectrometer was used to analyze the element content in the material. The specific operation steps were as follows: 0.4g of ternary positive electrode material was added to a conical flask, and then 60mL of pure water and 8mL of aqua regia were added, placed on a graphite heating platform, and digested at 375°C until clear. The obtained solution was diluted to 100mL using a volumetric flask and sampled and diluted, and then the diluted solution was analyzed for components to obtain the content of Li, Co, Ni, Mn and other elements in the positive electrode material.

[0149] (4) N Li (Lattice lithium) content

[0150] The lattice lithium content was obtained by subtracting the molar amount of residual lithium on the surface from the total molar amount of Li determined by ICP.

[0151] (5) Roughness test

[0152] The surface roughness of the positive electrode material was tested using a Bruker Dimension atomic force microscope, with the unit of nm. The surface of the positive electrode material was divided into 10 regions of equal area, and a 6μm×6μm test area was taken from each of the 10 regions. The probe of the atomic force microscope was used to measure the average and maximum values ​​of the surface roughness of the 10 test areas. The average values ​​of the surface roughness of the 10 test areas were summed up and then averaged to obtain the average surface roughness of the positive electrode material. The maximum values ​​of the surface roughness of the 10 test areas were summed up and averaged to obtain the maximum surface roughness of the positive electrode material.

[0153] (6) Electrochemical performance test:

[0154] 2025 button cells were used to test the electrochemical properties of the positive electrode materials.

[0155] The preparation process of 2025 button battery is as follows:

[0156] Preparation of electrode sheet: The multi-electrode positive electrode material, acetylene black and polyvinylidene fluoride (PVDF) were mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 95:3:2 to form a uniform slurry. The slurry was coated on aluminum foil and dried at 120°C for 12 hours. It was then stamped at a pressure of 100 MPa to form a positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm. The loading amount of the positive electrode material was 15 mg / cm 2 .

[0157] Battery assembly: In an argon-filled glove box with a water content and oxygen content of less than 5ppm, the positive electrode, separator, negative electrode and electrolyte were assembled into a 2025 button cell and left to stand for 6 hours. The negative electrode used a metal lithium sheet with a diameter of 17mm and a thickness of 1mm; the separator used a polyethylene porous membrane (Celgard2325) with a thickness of 25μm; the electrolyte was an equal mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) containing 1mol / L LiPF6.

[0158] Electrochemical performance test:

[0159] The electrochemical performance of the 2025 button cell was tested using the Shenzhen Xinwell battery testing system, with a charge and discharge current density of 200 mA / g at 0.1C.

[0160] The charge and discharge voltage range was controlled to be 3.0-4.3V. At room temperature, the button cell was charged and discharged at 0.1C to evaluate the first charge and discharge specific capacity and first charge and discharge efficiency of the multi-electrode material.

[0161] Cycle performance test:

[0162] The charge and discharge voltage range was controlled to be 3.0-4.3V. At a constant temperature of 45°C, the button battery was charged and discharged twice at 0.1C, and then charged and discharged 80 times at 1C to evaluate the high-temperature capacity retention rate of the multi-electrode material.

[0163] Rate performance test:

[0164] The charge and discharge voltage range was controlled to be 3.0-4.3V. At room temperature, the button cell was charged and discharged twice at 0.1C, and then charged and discharged once at 0.33C, 0.5C, 1.0C and 2C, respectively. The rate performance of the multi-element positive electrode material was evaluated by the ratio of the 0.1C first discharge capacity to the 1C discharge capacity. Among them, the 0.1C first discharge capacity is the discharge capacity of the button cell in the first cycle, and the 1C discharge capacity is the discharge capacity of the button cell in the sixth cycle.

[0165] (7) Thermal safety test

[0166] DSC (differential scanning calorimeter) is used to test the thermal stability of the material. The test method is: after discharging for 2 weeks, charge to 100% SOC, take out the electrode in the glove box, rinse the electrode with DMC (dimethyl carbonate) and dry it, scrape off the positive electrode powder and add it into the crucible, add the electrolyte calculated according to the amount of active material, seal the crucible and transfer it to the DSC test equipment for testing under nitrogen environment.

[0167] Table 1

[0168]

[0169]

[0170] As shown in Table 1, in Examples 1-14, the residual lithium content is significantly lower than that in Comparative Examples 1, 2, and 3, using aluminum oxide and cobalt oxide composite coating. This indicates that in Al / Co co-coating, Al can inhibit Co from being doped into the material, and only reacts with the residual lithium on the surface of the material, so the lattice lithium content is also higher. Li / N m =0.99-1.0. Because Al / Co co-coating is mainly concentrated on the particle surface, its surface roughness is also significantly higher than other composite coatings and single coatings. DSC test results show that Al / Co co-coating generally has a higher peak thermal temperature, indicating that Al / Co co-coating can better protect the surface structure of the material and improve the stability of the material structure.

[0171] In the first calcination process of Example 1-14, the first calcination is divided into a first insulation section and a second insulation section, and the temperature T1-1 of the first insulation section is 800-1200°C (excluding 800°C), the temperature T1-2 of the second insulation section is 600-800°C, and the insulation time t1 of the first insulation section and the insulation time t2 of the second insulation section satisfy: 2<t1 / t2<9, and the residual lithium content is significantly lower than that of Comparative Example 4. This shows that the first insulation section at 800-1200°C can promote the growth of single crystals, and the second insulation section at 600-800°C is more conducive to promoting the conversion of unreacted residual lithium into lattice lithium inside the material, thereby significantly reducing the residual lithium content on the surface of the positive electrode material.

[0172] In the second calcination process of Example 1-14, the second calcination is divided into a third insulation stage and a fourth insulation stage, the temperature T2-1 of the third insulation stage is 650-850°C, the temperature T2-2 of the fourth insulation stage is 500-650°C, and the insulation time t3 of the third insulation stage and the insulation time t4 of the third insulation stage satisfy: 1<t3 / t4<4, and the residual lithium content is significantly lower than that of Comparative Example 5. This shows that the third insulation temperature of 650-850°C (excluding 650°C) can promote the conversion of residual lithium on the surface of the positive electrode material into lattice lithium, and the temperature of the fourth insulation stage of 500-650°C can promote the conversion of residual lithium on the surface of the coating layer and the positive electrode material into lattice lithium.

[0173] Examples 1-14 use a composite coating of aluminum oxide and cobalt oxide, and the maximum surface roughness Rs is much higher than that of comparative examples 6-10. This shows that the composite coating of aluminum oxide and cobalt oxide is more conducive to the preparation of a high-roughness shell layer, thereby making the roughness of the local area of ​​the surface of the positive electrode material much greater than that of other areas, thereby effectively improving the processing performance of the positive electrode material and reducing the charge transfer impedance of the lithium-ion battery. At the same time, the lower roughness formed in other areas also has a larger specific surface area, which can produce more lithium ion embedding points, which is beneficial to improving the rate performance of the battery.

[0174] In Comparative Example 11, the amount of aluminum source and cobalt source used is too large, resulting in the maximum surface roughness of the positive electrode material being greater than 500nm, Ra>50nm, which in turn makes the roughness of the local area of ​​the positive electrode material surface too large, and the roughness of the remaining areas is also high, resulting in fewer lithium ion embedding points, which is not conducive to improving the capacity and cycle stability of the battery.

[0175] Table 2

[0176]

[0177]

[0178] As shown in Table 2, Examples 1-14 use Al / Co co-coating, and their surfaces have more Al / Co composite lithium compounds, which can significantly improve the discharge capacity, rate performance, and high-temperature cycle performance of the material compared to Comparative Examples 1-3.

[0179] In Example 1-14, during the first calcination process, the first calcination is divided into a first insulation section and a second insulation section, and the temperature T1-1 of the first insulation section satisfies 800<T1-1≤1200℃, the temperature T1-2 of the second insulation section satisfies 600≤T1-2≤800℃, and the insulation time t1 of the first insulation section and the insulation time t2 of the second insulation section satisfy: 2<t1 / t2<9, and its residual lithium content is significantly lower than that of Comparative Example 4, thereby having more excellent discharge capacity, rate performance and high temperature cycle performance.

[0180] In Example 1-14, during the second calcination process, the second calcination is divided into a third insulation stage and a fourth insulation stage, the temperature T2-1 of the third insulation stage satisfies 650<T2-1≤850℃, the temperature T2-2 of the fourth insulation stage satisfies 500≤T2-2≤650℃, and the insulation time t3 of the third insulation stage and the insulation time t4 of the third insulation stage satisfy: 1<t3 / t4<4, and its residual lithium content is significantly lower than that of Comparative Example 5, thereby having more excellent discharge capacity, rate performance and high temperature cycle performance.

[0181] Examples 1-14 use a composite coating of aluminum oxide and cobalt oxide, and the maximum surface roughness Rs is much higher than that of comparative examples 6-10. This shows that the composite coating of aluminum oxide and cobalt oxide is more conducive to the preparation of a high-roughness shell layer, thereby making the roughness of the local area of ​​the surface of the positive electrode material much greater than that of other areas, thereby effectively improving the processing performance of the positive electrode material and reducing the charge transfer impedance of the lithium-ion battery. At the same time, the lower roughness formed in other areas also has a larger specific surface area, which can produce more lithium ion embedding points, which is beneficial to improving the rate performance of the battery.

[0182] In Comparative Example 11, the amount of aluminum source and cobalt source used is too large, resulting in the maximum surface roughness of the positive electrode material being greater than 500nm, which in turn makes the roughness of the local area of ​​the positive electrode material surface too large, and the roughness of the remaining areas is also high, resulting in fewer lithium ion embedding points, which is not conducive to improving the capacity and cycle stability of the battery.

[0183] Figure 3 shows a SEM image of the positive electrode material provided in Example 1; Figure 4 The SEM image of the positive electrode material provided in Comparative Example 1 is shown; Figure 5 The SEM image of the positive electrode material provided in Comparative Example 2 is shown; Figure 6 The SEM image of the positive electrode material provided in Comparative Example 6 is shown; Figure 7 The SEM image of the positive electrode material provided in Comparative Example 7 is shown.

[0184] from Figure 3 It can be seen that the positive electrode material provided in Example 1 forms a uniform coating layer, and the particle surface is rough with a high roughness.

[0185] from Figure 4 It can be seen that the surface of the positive electrode material particles provided in Comparative Example 1 is smooth and no obvious coating layer is formed.

[0186] from Figure 5 It can be seen that the surface of the positive electrode material provided in Comparative Example 2 is smooth and no obvious coating layer is formed.

[0187] from Figure 6It can be seen that the positive electrode material provided in Comparative Example 6 forms a coating layer, but the roughness of the particle surface is significantly lower than that of Example 1.

[0188] from Figure 7 It can be seen that the positive electrode material provided in Comparative Example 7 forms a coating layer, but the roughness of the particle surface is significantly lower than that of Example 1.

[0189] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes a matrix material and a shell material at least partially coated on the surface of the matrix material. The matrix material includes nickel element, cobalt element and manganese element, and the shell material includes Al element and Co element; The positive electrode material satisfies: 6 < Rs / Ra ≤ 17.5, 300nm < Rs < 500nm, where Ra is the surface average roughness of the positive electrode material and Rs is the surface maximum roughness of the positive electrode material; 0.98<N Li / N m <1.00, N Li It represents the molar amount of lattice Li in the positive electrode material per unit mass, N m It represents the total molar amount of nickel, cobalt and manganese in the positive electrode material per unit mass.

2. The positive electrode material according to claim 1, characterized in that 28nm ≤ Ra < 50nm.

3. The positive electrode material according to claim 1, characterized in that Q=0.5*Rs / Ra+2.0*N Li / N m ,5.5≤Q≤10.5; And / or, 30nm ≤ Ra ≤ 40nm, 300nm < Rs < 400nm, and 8 < Rs / Ra < 13.

5.

4. The positive electrode material according to claim 1, wherein The surface residual lithium content of the positive electrode material < 1500ppm; And / or, the volume median diameter D50 of the positive electrode material is 2 - 8μm; And / or, the positive electrode material is a single crystal material and includes grains with the same orientation, and the grain size is 0.5 - 3μm; And / or, the specific surface area of ​​the positive electrode material is S, 0.4≤S≤0.8m 2 / g.

5. The positive electrode material according to claim 1, wherein The tap density of the positive electrode material is: 1.2~1.9g / cm 3 ; And / or, the compaction density of the positive electrode material is: 2.8~3.3g / cm 3 ; and / or, N Li It is 0.96~1.01mol.

6. The positive electrode material according to claim 1, wherein The content of Al element in the positive electrode material is 1000ppm - 3000ppm; And / or, the content of Co element in the positive electrode material is 30000ppm - 85000ppm.

7. The positive electrode material according to any one of claims 1 to 5, characterized in that The chemical general formula of the matrix material is , and the chemical general formula of the shell material is Li a Al b Co c O2. The chemical general formula of the positive electrode material is , where 0.96 < α < 0.98, 0.9 < a < 1.2, 0.1 < b < 0.2, 0.7 < c < 0.9, 0.98 ≤ ≤ 1.01, 0.8 < x < 1, 0 < y < 0.2, 0 < z < 0.2, x + y + z = 1, M1 is a doping element, and M1 is selected from at least one of A1, Co, Zr, B, Ti, Ca, Ce, Zn, Cr, Mg, Y, La, Sr, Ba, W, Mo, Nb, Si, and Sb.

8. A method for preparing a positive electrode material, characterized in that: A method for preparing the positive electrode material according to any one of claims 1 to 7, comprising: Step S1, mixing a matrix material precursor, a lithium source and an optional dopant, and performing a first calcination to obtain a first positive electrode material intermediate; Step S2, mixing the first positive electrode material intermediate with a cobalt source and an aluminum source, and performing a second calcination to obtain the positive electrode material; Wherein, the matrix material precursor is a nickel-cobalt-manganese ternary positive electrode material precursor; The dopant is selected from at least one of carbonates, hydroxides, hydroxyoxides, oxides or acetates of M1.

9. The preparation method according to claim 8, characterized in that: The addition amount of the aluminum source satisfies: 0 < [n(Al)] / [n(Ni)+n(Co)+n(Mn)] ≤ 0.03; And / or, the addition amount of the cobalt source satisfies: 0 < [n(Co)] / [n(Ni)+n(Co)+n(Mn)] ≤ 0.04; And / or, the addition amount of the lithium source satisfies: 1.04 ≤ [n(Li)] / [n(Ni)+n(Co)+n(Mn)] ≤ 1.08; And / or, the first positive electrode material intermediate satisfies: 1.02 ≤ [n(Li)] / [n(Ni)+n(Co)+n(Mn)] ≤ 1.

06.

10. A battery, characterized in that: The battery includes a positive electrode material, and the positive electrode material includes the positive electrode material according to any one of claims 1 to 7 or the positive electrode material obtained by the preparation method according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Nickel-cobalt-lithium manganate ternary cathode material and preparation method thereof

    CN110474026A

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN114400317A

  • Ternary positive electrode material for lithium ion battery and preparation method of ternary positive electrode material

    CN116741980A

  • Positive electrode active material for lithium secondary battery, manufacturing method of same, and lithium secondary battery comprising same

    WO2024136307A1